Pectoralis major muscle free flap:: anatomical studies on pedicle length and vessel diameter - Trainotti, Susanne; Rotter, Nicole; Veit, Johannes Adrian (ENT, 2019)
Large and deep defects resulting from lateral skull base surgery represent a challenge to the head and neck surgeon. Different microvascular free flaps have spe...
Gesehen am 07.01.2020